Redox-dependent functional switching of plant proteins accompanying with their structural changes - Chi, Yong Hun; Paeng, Seol Ki; Kim, Min Ji; Hwang, Gwang Yong; Melencion, Sarah Mae B.; Oh, Hun Taek; Lee, Sang Yeol (Frontiers in Plant Science, 2013)
Reactive oxygen species (ROS) can be generated during the course of normal aerobic metabolism or when an organism is exposed to a variety of stress conditions. It can cause a widespread damage to intracellular macromolecules and play a causal role in many degenerative diseases. Like other aerobic organisms plants are also equipped with a wide range of antioxidant redox proteins, such as superoxide dismutase (SOD), catalase, glutaredoxin (Grx), thioredoxin (Trx), Trx reductase (TR), protein disulfide reductase (PDI), and other kinds of peroxidases that are usually significant in preventing harmful effects of ROS. To defend plant cells in response to stimuli, a part of redox proteins have shown to play multiple functions through the post-translational modification with a redox-dependent manner. For the alternative switching of their cellular functions, the redox proteins change their protein structures from low molecular weight (LMW) to high molecular weight (HMW) protein complexes depending on the external stress. The HMW proteins are reported to act as molecular chaperone, which enable the plants to enhance their stress tolerance. In addition, some transcription factors and co-activators have function responding to environmental stresses by redox-dependent structural changes. This review describes the molecular mechanism and physiological significance of the redox proteins, transcription factors and co-activators to protect the plants from environmental stresses through the redox-dependent structural and functional switching of the plant redox proteins.